Assessment of Irrigation Practices of Farmers Receiving Water from Open-Canal and Piped Irrigation Networks - Nihan Körpe Aslan; Murat Tekiner (Turkish Journal of Agriculture: Food Science and Technology)
Open-canal irrigation networks have been transformed into closed-piped networks. Drip irrigation is the most common method used irrigations in Çanakkale province. The aim of study is to assess irrigation practices of farmers using different irrigation networks. There were not significant differences in irrigation practices of the farmers receiving water from both networks, but all were making mistakes and unconscious in their practices. An optimum schedule was also prepared to compare with farmer practices. While a farmer growing tomato in Kumkale village with piped-network was expected to apply 531 mm irrigation water as seasonal total, present farmer applied 1414 mm water; while a farmer growing tomato in Mahmudiye village with open-canal network was expected to apply a total of 457 mm, present farmer applied 492 mm irrigation water; while a farmer growing maize in Kumkale village with piped-network was expected to apply 512 mm, the present farmer applied 975 mm; finally a farmer growing maize in Mahmudiye village with open-canal network was expected to apply 379 mm water, the present farmer applied 228 mm irrigation water throughout the entire growing season. Irrigation water efficiency (IWUE) values indicating the effects of irrigation water quantities on yields were calculated as 2.5 kg/da/mm for tomato culture in Kumkale; 12.3 kg/da/mm for tomato culture in Mahmudiye; 0.7 kg/da/mm for maize culture in Kumkale and 8,7 kg/da/mm for maize culture in Mahmudiye village. Relative irrigation supply (RIS) values indicating how efficiently the precipitations were used were calculated as 2.98 for tomato culture in Kumkale; 1.41 for tomato culture in Mahmudiye; 2.40 for maize culture in Kumkale and 0.85 for maize culture in Mahmudiye village.